Suzaku observations of Jovian diffuse hard X-ray emission. (9th June 2021) - Numazawa, Masaki; Ezoe, Yuichiro; Ohashi, Takaya; Ishikawa, Kumi; Miyoshi, Yoshizumi; Shiota, Daikou; Uchiyama, Yasunobu; Kimura, Tomoki; Branduardi-Raymont, Graziella
Abstract: We report on results of systematic analyses of the entire three X-ray data sets of Jupiter taken by Suzaku in 2006, 2012, and 2014. Jovian diffuse hard X-ray emission was discovered by Suzaku in 2006 when the solar activity went toward its minimum. The diffuse emission was spatially consistent with the Jovian inner magnetosphere and was spectrally fitted with a flat power-law function suggesting non-thermal emission. Thus, a scenario in which ultra-relativistic (tens of MeV) electrons in the Jovian inner magnetosphere inverse-Comptonize solar visible photons into X-ray bands has been hypothetically proposed. We focused on the dependence of the Jovian diffuse hard X-ray emission on the solar activity to verify this scenario. The solar activity in 2012 and 2014 was around the maximum of the 24th solar cycle. By combining the imaging and spectral analyses for the three data sets, we successfully separated the contribution of the diffuse emission from the emission of Jupiter's body (i.e., the aurora and disk emission). The 1–5 keV luminosity of the diffuse emission has been stable and did not vary significantly, and did not simply depend on the solar activity, which is also known to affect the high-energy electron distribution in the Jovian inner magnetosphere scarcely. The luminosity of the body emission both in 0.2–1 and 1–5 keV, in contrast, probably depended on the solar activity and varied by a factor of 2–5. These results strongly supported the inverse-Compton scattering scenario by the ultra-relativistic electrons. In this paper, we estimate spatial and spectral distributions of the inverse-Compton scattering X-rays by Jovian magnetospheric high-energy electrons with reference to the Divine–Garrett model and found a possible agreement in an inner region (≲10  R J ) for the X-ray observations.